2023
DOI: 10.1002/brb3.3181
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo‐mutual gazing enhances interbrain synchrony during remote joint attention tasking

Abstract: IntroductionMutual gaze enables people to share attention and increase engagement during social interactions through intentional and implicit messages. Although previous studies have explored gaze behaviors and neural mechanisms underlying in‐person eye contact, the growing prevalence of remote communication has raised questions about how to establish mutual gaze remotely and how the brains of interacting individuals synchronize.MethodsTo address these questions, we conducted a study using eye trackers to crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 104 publications
0
0
0
Order By: Relevance
“…Relatively few studies have explored increased IBS in competitive compared to the cooperative contexts [21,22,32]. In line with the latest EEG studies demonstrating cooperation and competition using different paradigms, our results also reveal a greater IBS in the frontal brain regions and lower frequency bands during cooperation.…”
Section: Increased Inter-brain Synchronization During Competitionsupporting
confidence: 90%
See 4 more Smart Citations
“…Relatively few studies have explored increased IBS in competitive compared to the cooperative contexts [21,22,32]. In line with the latest EEG studies demonstrating cooperation and competition using different paradigms, our results also reveal a greater IBS in the frontal brain regions and lower frequency bands during cooperation.…”
Section: Increased Inter-brain Synchronization During Competitionsupporting
confidence: 90%
“…Although our results in Fig. 8 demonstrated greater IBS in most frequency bands, including delta, theta, alpha, and beta oscillations, several recent studies, encompassing both cooperation and competition modes, have reported no findings in alpha and beta IBS [21,22]. Nevertheless, some studies using cooperative tasks have found that alpha, beta, or even gamma IBS has been observed during joint action or cooperation [3,21,23,24,34].…”
Section: Increased Inter-brain Synchronization During Competitioncontrasting
confidence: 70%
See 3 more Smart Citations